PCK OF PROSPECTIVE MATHEMATICS TEACHERS’ THROUGH COLLABORATIVE ONLINE LEARNING - lestari, Wiwit Damayanti; Pakhrurrozi, Imam; Mellawaty, Mellawaty; Rusmayadi, Muh.; Taufan, Mochammad (Pedagogy: Jurnal Pendidikan Matematika, 2025)
Teachers play a determining role in students' success in achieving learning goals. Therefore, Pedagogical Content Knowledge is an ability that teachers and prospective teachers must have. This research aims to describe the Pedagogical Content Knowledge profile of prospective mathematics teachers in collaborative online learning, especially in courses evaluating mathematics learning processes and outcomes. This research is descriptive qualitative research. Prospective mathematics teacher students who contracted courses in evaluating the process and results of mathematics learning from Wiralodra University and Nahdlatul Wathan University of Mataram, were the subjects of this research. The instruments used in this research were a test of understanding the concept of evaluating mathematics learning processes and outcomes, questionnaires, and learning documentation via the Phytagoras LMS. The data analysis techniques used include data reduction stages, data presentation, and drawing conclusions. Based on the research results, it was found that students in the mathematics learning process and outcome evaluation course whose lectures were held collaboratively online had a very good Pedagogical Content Knowledge profile and gave a positive response to the implementation of collaborative online learning.